AB0140 Correlation between dermal thickness and blood perfusion in different skin areas of systemic sclerosis patients. (23rd January 2014) - Ruaro, B.; Sulli, A.; Bernero, E.; Alessandri, E.; Zampogna, G.; Cimmino, M. A.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) is characterized by decreased peripheral blood perfusion (BP) and increased dermal thickness (DT) (1 -3 ). Objectives: The aim of this study was to identify possible correlations between BP and DT in three different areas of skin (periungual, dorsum of hand and zygoma) in SSc patients. Methods: Sixty-three SSc patients (mean age 64±11SD years) were enrolled after written informed consent. BP was analysed by new technique laser speckle contrast analysis (LASCA) at the level of dorsal region of hands and face in both SSc patients and healthy subjects (4 ). Different regions of interest (ROI) were created at level of periungual areas of the 3 rd finger bilaterally, dorsum of both hands and zygomas, and the average BP was scored as perfusion units (PU). Both high frequency ultrasound (US) and modified Rodnan skin score (mRss) were used to evaluate average DT at the level of dorsum of 3 rd finger, hand and zygoma bilaterally (5 ). US and LASCA were also performed in 63 age and sex matched healthy subjects. Statistical evaluation was carried out by non parametric tests. Results: A negative correlation was observed between BP and both ultrasound-DT (p=0.0005) and mRss (p=0.007) in SSc patients at the level of fingers. No statistically significant correlation was found between BP and both ultrasound-DT and mRss at level of dorsum of hands and zygomas in SSc patients. In healthy subjects no statistically significant correlation was detected between BP and DT evaluated by both US and mRss at the level of fingers, dorsum of hands or zygomas. SSc patients showed a statistically significant lower BP at level of periungual areas when compared with healthy subjects (p<0.0001). No statistically significant difference in BP values was observed between SSc and healthy subjects at the level of dorsum of hand and zygomas. SSc patients showed a statistically significant higher ultrasound-DT at the level of periungual areas, dorsum of hands and zygomas than healthy subjects (p<0.0001, for all). A statistically significant positive correlation was observed between ultrasound and mRss concerning DT evaluation in SSc patients at level of the three areas (periungual p<0.0001; dorsum of hand p=0.03; zygoma p=0.0001). Conclusions: This study demonstrates a relationship between periungual BP evaluated by LASCA and finger DT evaluated by both US and mRss in SSc patients. SSc patients have a statistically significant higher DT at level of dorsum of finger, hand or zygoma than healthy subjects. There is a significant positive correlation between US and mRss in the assessment of DT. References: Cutolo M, et al. J Rheumatol 2010; 37:1174-80. Rosato E, et al. Rheumatology 2011;50:1654-8. Moore TL, et al. Rheumatology 2003; 42: 1559-63. Draijer M et al. Laser Med Sci 2009; 24: 639-51. Kaloudi O et al. Ann Rheum Dis. 2010; 69:1140-3. Disclosure of Interest: None Declared